Respuesta :
Answer:
-43K+17
Step-by-step explanation:
(–9k3 + 12k2 + 9) – (10k3 + 3k2 + 4k – 8)
-9.3=-27 10.3=30
12.2=24 3.2=6
=(-27k+24k+9) - (30k+6k+4k-8)
COLLECT LIKE TERMS
=(-3k+9) - (40K-8)
= -3k+9-40k+8
= -43k+17
Answer:
-19k³ + 9k² + 17
Step-by-step explanation:
Given expression;
(-9k³ + 12k² + 9) - (10k³ + 3k² + 4k - 8)
To simplify, expand the brackets.
In the second bracket, the negative sign multiplies through;
= (-9k³ + 12k² + 9) - 10k³ - 3k² - 4k + 8
= -9k³ + 12k² + 9 - 10k³ - 3k² - 4k + 8
= -9k³ - 10k³ + 12k² - 3k²+ 9+ 8
= -19k³ + 9k² + 17